Protein kinase Cδ knockout mice are protected from cocaine-induced hepatotoxicity. (5th January 2019) - Mai, Huynh Nhu; Lee, Sung Hoon; Sharma, Garima; Kim, Dae-Joong; Sharma, Naveen; Shin, Eun-Joo; Pham, Duc Toan; Trinh, Quynh Dieu; Jang, Choon-Gon; Nah, Seung-Yeol; Jeong, Ji Hoon; Kim, Hyoung-Chun
Abstract: We investigated whether protein kinase Cδ (PKCδ) mediates cocaine-induced hepatotoxicity in mice. Cocaine treatment (60 mg/kg, i.p.) significantly increased cleaved PKCδ expression in the liver of wild-type (WT) mice, and led to significant increases in oxidative parameters (i.e., reactive oxygen species, 4-hydroxylnonenal and protein carbonyl). These cocaine-induced oxidative burdens were attenuated by pharmacological (i.e., rottlerin) or genetic depletion of PKCδ. We also demonstrated that treatment with cocaine resulted in significant increases in nuclear factor erythroid-2-related factor 2 (Nrf-2) nuclear translocation and increased Nrf-2 DNA-binding activity in wild-type (WT) mice. These increases were more pronounced in the rottlerin-treated WT or PKCδ knockout mice than in the saline-treated WT mice. Although cocaine treatment increased Nrf-2 nuclear translocation, DNA binding activity, and γ-glutamyl cysteine ligases (i.e., GCLc and GCLm) mRNA expressions, while it reduced the glutathione level and GSH/GSSG ratio. These decreases were attenuated by PKCδ depletion. Cocaine treatment significantly increased alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels in the serum of WT mice signifying the hepatic damage. These increases were also attenuated by PKCδ depletion. In addition, cocaine-induced hepatic degeneration in WT mice was evident 1 d post-cocaine. At that time, cocaine treatment decreased Bcl-2 and Bcl-xL levels, and increased Bax, cytosolic cytochrome c, and cleaved caspase-3 levels. Pharmacological or genetic depletion of PKCδ significantly ameliorated the pro-apoptotic properties and hepatic degeneration. Therefore, our results suggest that inhibition of PKCδ, as well as activation of Nrf-2, is important for protecting against hepatotoxicity induced by cocaine. Graphical abstract: Highlights: Cocaine induces hepatotoxicity via oxidative stress and activation of PKCδ. Depletion of PKCδ protects from cocaine-induced hepatotoxicity. Depletion of PKCδ exerts antioxidant activity via Nrf2-related glutathione system.